Characteristics of Patient with Proliferative Diabetic Retinopathy Underwent Anti-Vascular Endothelial Growth Factors Injection in Cicendo Eye Hospital, Bandung in January–December 2013 - Marsha Rayfa Pintary; Arief S. Kartasasmita; Juliati Juliati (Althea Medical Journal, 2016)
Background: Proliferative Diabetic Retinopathy (DR) is one of the microvascular complications of diabetes mellitus (DM) that is prevalent to the blindness risk. The World Health Organization (WHO) considers Proliferative DR one of the priorities of eye diseases. This disease is caused by angiogenesis brought about by Vascular Endothelial Growth Factors (VEGF). The Anti-VEGF Bevacizumab (Avastin) injection is considered sufficient in preventing proliferative DR patients from blindness. This study aimed to identify the characteristics of patients with proliferative DR underwent Anti-VEGF injection at Cicendo Eye Hospital, Bandung.Methods: This was a retrospective study conducted from August−October 2014 using 40 medical records of patients with proliferative DR underwent Anti-VEGF Bevacizumab (Avastin) injection at the Cicendo Eye Hospital Bandung from January−December 2013. Inclusion criteria were the patients underwent anti-VEGF injection with complete medical records with minimum follow up of 3 weeks.Results: Among 40 patients, 55% were male and 45% were female. Furthermore, there was 100% found for DM Type 2. Moreover, random blood glucose varied among 140–200mg/dl (50%), while the hypertension was mostly at stage 2. Some of these patients had proliferative DR with vitreal hemorrhage (25%), macular edema (40%), and/or tractionalablasio retina (22.5%). Most patients had an improvement in their visual acuity (60%).Conclusions: Most of patients are male, aged 50–59 years old, random blood glucose among 140– 200mg/dl, followed DM Type 2 and hypertension stage 2. Anti-VEGF injection improves visual acuity. [AMJ.2016;3(2):280–5]DOI: 10.15850/amj.v3n2.781